A comprehensive study on antidiabetic and antibacterial activities of ZnO nanoparticles biosynthesized using Silybum marianum L seed extract - Mohammadi Arvanag, Farid; Bayrami, Abolfazl; Habibi-Yangjeh, Aziz; Rahim Pouran, Shima (Elsevier, 2019)
Green synthesis of ZnO nanoparticles (NPs) using the plants’ extract and their potential application have driven a tremendous interest in recent years. This study reports a green microwave-assisted method for synthesis of ZnO NPs using Silybum marianum L. seed extract. Characteristics of the as-prepared sample was explored in terms of crystalline phase, morphology, composition, surface area, optical, and thermal properties. The particles of the biosynthesized sample (ZnO/extract) had smaller sizes than the chemically produced one (ZnO). The existence of biomolecules from Silybum marianum L seed extract linked to the ZnO/extract sample was approved by various analyses. The ZnO/extract sample was used for treating alloxan-induced diabetic rats and its efficiency was compared with ZnO, extract, and insulin treatments. For this purpose, the levels of blood glucose, insulin, total cholesterol, total triglyceride, and high-density lipoprotein were measured before and after treating with the studied treatment agents and compared with each other. Moreover, the antibacterial activities of both ZnO samples were investigated against E. coli to assess their potential antibacterial application. From the results, ZnO/extract NPs represented an outstanding performance in overcoming the diabetic disorders and good antibacterial activity against the studied bacteria.